High prevalence of metabolic syndrome among overweight adults in Vietnam based on different criteria: Results from a community-based study - Sang Ngoc Nguyen, PhD; Van Dinh Tran, PhD; Trinh Thi Mai Le, MD; Hoang Thu Nga, MD; Nguyen Thi Thi Tho, PhD (Elsevier, 2021)
Background: The aim of this study was to identify the prevalence of Metabolic Syndrome (MetS) and its components among overweight adults in a rural region Vietnam based on the International Diabetes Federation (IDF), 2005 and the Joint Interim Statement (JIS) 2009 definitions, and determine the level of agreement between these definitions. Methods: A sample of 1076 overweight adults aged 50-65 in 10 randomly selected communes in Phu Ly district, Hanam province, Vietnam were selected into the study. Study participants were collected fasting venous blood samples by certified phlebotomists. Anthropometric measures were also performed to obtain weight, height, waist circumference. MetS was defined using the IDF (2005), and the JIS (2009) definitions. The level of agreement between the two definitions was indicated by the sensitivity, specificity, and the Kappa index. Results: The prevalence of MetS among the overweight adults was 41.6%, and 44.0% based on the IDF (2005), and the JIS (2009) definition, respectively. The MetS prevalence among females was higher than that among males in the two definitions. The level of agreement between the two definitions was excellent (Kappa index = 0.987, p < 0.001). Conclusion: The JIS (2009) definition identified more Vietnamese overweight adults with MetS compared to the IDF (2005) criteria, 44.0%, and 41.6%, respectively. Females showed to be having higher prevalence in comparison to males regardless the definitions used. Excellent agreement between the two criteria was found.